Characterization of Avt1p as a vacuolar proton/amino acid antiporter in Saccharomyces cerevisiae. Issue 5 (4th May 2015) - Tone, Junichi; Yoshimura, Ayumi; Manabe, Kunio; Murao, Nami; Sekito, Takayuki; Kawano-Kawada, Miyuki; Kakinuma, Yoshimi
Abstract: Several genes for vacuolar amino acid transport were reported in Saccharomyces cerevisiae, but have not well been investigated. We characterized AVT1, a member of the AVT vacuolar transporter family, which is reported to be involved in lifespan of yeast. ATP-dependent uptake of isoleucine and histidine by the vacuolar vesicles of an AVT exporter mutant was lost by introducing avt1 ∆ mutation. Uptake activity was inhibited by the V-ATPase inhibitor: concanamycin A and a protonophore. Isoleucine uptake was inhibited by various neutral amino acids and histidine, but not by γ-aminobutyric acid, glutamate, and aspartate. V-ATPase-dependent acidification of the vesicles was declined by the addition of isoleucine or histidine, depending upon Avt1p. Taken together with the data of the amino acid contents of vacuolar fractions in cells, the results suggested that Avt1p is a proton/amino acid antiporter important for vacuolar compartmentalization of various amino acids. Abstract: : Avt1p is a proton/amino acid antiporter involved in vacuolar uptake of histidine and various neutral amino acids